Ḥadīṯ Scholar and Historiography: Some Reflections on the Sīra Corpora of Ibn Ḥibbān al-Bustī's (d. 354/965) Kitāb al-Ṯiqāt - Yusoff, Muhammad Fawwaz Bin Muhammad (Arabica, 2019)
In a recent volume of the Encyclopaedia of Arabic Literature, Ibn Ḥibbān is credited as the author of the Kitāb al-Ṯiqāt, and is described as "a widely travelled traditionist and prolific writer." The Kitāb al-Ṯiqāt is one of the most valuable sources for the study of the biographies of the transmitters of the ḥadīṯs over the first three centuries and is a record of medieval Islamicate history, even including non-ḥadīṯ transmission. The subject of the Kitāb al-Ṯiqāt is the Prophet's sīra, the history of caliphs and kings, biographies of Companions, ḥadīṯ transmitters, legal theorists, theologians, and many others. In this brief article, an attempt is made to describe Ibn Ḥibbān's approach to the sīra of the Prophet, in order to arrive at some general considerations on the relationship between ḥadīṯ studies and historiography. The tarāgim (chapter titles) and narrative arrangement of the Kitāb al-Ṯiqāt give insight into Ibn Ḥibbān's expositions, and demonstrate that his interest goes beyond the science of ḥadīṯ transmission.